IMPLICATIONS OF COVID-19 ON TEXTILES INDUSTRY IN INDIA - DISCOVERING ISSUES AND CHALLENGES ON DEMAND AND SUPPLY SIDES - ARAVAMUDHAN Varadaraj; SAI MOHANRAJ Prasanna; SENGODAN Ananth (Eastern European Journal of Regional Studies)
The unexpected COVID-19 outbreak has threatened the world and derailed the socio-economic lives of people. In this context, this study is aimed to discuss the implications of COVID-19 in textiles sector in India along with major issues and challenges on demand and supply sides. This study determines the impact of crisis which affected demand and supply in textiles and fashion industry. COVID-19 has several implications for this industry, be it from demand or production. Its presence is observed in different aspects of the industry. This study uses secondary data collected from various sources like studies published in peer-reviewed journals. This study focuses on the need to think differently to deal with this unexpected crisis. Relaxation of tax compliance rules and deadlines, especially for small-scale segments is one of the potential solutions, so that the conditions of customer demand are not affected directly. In addition, more comprehensive financial relief package could be announced for textiles sector, considering the export- and labor-intensive processes to stem the adverse effects of pandemic. Rebates on exporters could be the next major step against the remission of taxes or duties on exports. This study was conducted during the COVID-19 crisis. More studies would be needed in post COVID era to generalize the findings. The combative measures and actual impact may be evolutionary and dynamic. The analysis focuses on the “out of the box” thinking to deal with unexpected crisis, but it may have different aspects to be discussed as the crisis unfolds. There is a lack of significant research on the impact of COVID-19 on textile industry in India. This study could be the stepping stone for researchers to study the impact on textiles sector and help policymakers to prepare for unexpected crises in future.